Wordwall application in growing the interest of religious learning students of SMK Muhammadiyah 4 Banjarmasin - Muhammad Yazid Maulidi; Ani Cahyadi (Universitas Lambung Mangkurat, 2024)
Educational technology is often assumed in the perception that leads solely to the problem of electronics or technical equipment only, whereas educational technology contains a very broad understanding and application. The progress of global technology has been influential in all aspects of life both in economics, politics, art culture and even in education. The world of education must be willing to hold a positive innovation for the advancement of education and schools. One of the products of that educational technology is wordwall. Wordwall application has become one of the innovative learning tools in the context of Islamic Religious Education. . This research explores the use of Wordwall application in improving the effectiveness of learning Islamic Religious Education subjects at the high school level and above. Experimental research methods are used by involving a group of students as research subjects. This study aims to evaluate the impact of the use of Wordwall application on the understanding of Islamic religious concepts, student involvement, and their learning interests. The results showed that the use of Wordwall application in Islamic Religious Education Learning significantly improve students ' understanding of religious concepts, as well as encourage student involvement in the learning process. Students show greater interest in learning Islamic religious material when using the Wordwall app, which offers an interactive and engaging format. In this context, the Wordwall app has proven to be an effective tool in improving the learning of Islamic Religious Education in schools. The implications of this study indicate that the integration of technology in Islamic religious learning can enrich the learning experience of students and support their understanding of religious concepts in a more comprehensive and enjoyable.